PENGARUH PROFESIONALISME AUDIT, INTENSITAS MORAL UNTUK MELAKUKAN TINDAKAN WHISTLEBLOWING (STUDI PADA KAP DI INDONESIA) - Yulita Zanaria (Akuisisi: Jurnal Akuntansi, 2016)
Purpose – The purpose of this paper is to to investigate the influence of   professionalism auditor and  intensity of moral  to  effect on whistleblowing action  of  KAP  in IndonesiaDesign/methodology/approach-  The research method used is the population of all auditors who worked on 25 KAP in Indonesia. Sampling technique using nonprobabilitas or not random with convienience sampling method.Tool using regression analysis using F test and t test with SPSS ver.17.00. The paper ends with a set of hypotheses requiring further research. Findings – The paper finds that the professionalism auditor, intensity of moral  simultaneously affect on whistleblowing action  of  KAP  in Indonesia.  professionalism auditor variable partially significant affect on whistleblowing action  of  KAP  in Indonesia. Variable intensity of moral  has an effect on whistleblowing action  of  KAP  in Indonesia Originality/value –This paper provides influence of   professionalism auditor , intensity of moral , to  effect on whistleblowing action  of  KAP  in Indonesia Keywords: Professionalism auditor , intensity of moral , effect on whistleblowing action  Paper type General review